Irritable Bowel Syndrome among Street Vendors in Bangladesh - Haque, Faridul; Aftab, Hafeza (Bangladesh Journal of Medicine, 2024)
Background: Irritable Bowel Syndrome (IBS) is a common functional gastrointestinal disorder with 8.5% prevalence rate in Bangladesh. The objectives of this study were to assess the prevalence of IBS and to determine the subtypes of IBS among street vendors in Bangladesh. Methods: This observational cross-sectional study was conducted among various street vendors in Dhaka South City Corporation (DSCC) from March 2022 to August 2023. Initially 156 vendors were approached. Among them 133 were responders and 23 were non responders. Following exclusion criteria, 115 were interviewed face to face. The diagnosis and sub typing of IBS was done following Rome IV criteria and Bristol Stool Form Scale. Results: Among 115 study participants 95 were male and 20 were female. Eighty percent of them was fruit seller. The mean age of the study participants was 38.54 ± 13.03 years. Among them, 101 were Non-IBS and 14 were IBS . The overall prevalence of IBS was 12.17%. Majority of the participants(14.3%) was in the 35-50 years age group. Among 14 IBS participants, 8 had constipation predominant (IBS-C), 2 had diarrhea predominant (IBS- D) and 4 had mixed type IBS (IBS-M). There was no unclassified IBS (IBS-U) subject was found .There was significant difference in bowel frequency and physician consultation pattern. Conclusion: Prevalence of IBS among street vendors in Bangladesh was 12.7% with constipation predominant (IBS-C). Bangladesh J Medicine 2024; Vol. 35, No. 2, Supplementation: 170-171